Women in the History of Academic Science in Bulgaria - Ivanova, Dzheni (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2017)
The goal of this paper is to present the project “Women in the history of academic science in Bulgaria” of the BAS Scientific Archive. In this regard, will be created an encyclopedic reference book and an archival database about the academic career of women. The expected scientific results are as follows: establishment of an information body with free access to the materials and options to extract concepts from them; building a comprehensive interdisciplinary theoretical framework for analysis of information on women in science; the popularization of themed archives will enrich the vision of women history and science history, as well as about the cultural and historical heritage.